Penerapan Prinsip Persaingan Usaha Atas Pelaksanaan E-Purchasing dalam Pengadaan Barang Jasa Pemerintah - Prasetia, Ira Kurnia; Soleh, Moh (CV. Era Digital Nusantara, 2024)
In the context of developing MSMEs in the world of E-commerce, the Government also provides government goods/services procurement platform facilities that can be accessed by MSME business people to take part in providing goods/services using a method termed Epurchasing or electronic purchasing. The existence of the Electronic Catalog and the EPurchasing process is intended as a media/platform and an easy alternative procurement process for actors procuring Government Goods/Services. A transparent and open Electronic Catalog creates a competitive business climate, encourages the development of product quality at reasonable product prices, thus encouraging growth in the performance of Domestic Business Actor partners. Apart from that, through the implementation of the Electronic Catalogue, the Government also obtains accurate reports on transactions for purchases of Goods/Services at Ministries/Institutions/Regional Governments.